Analysis of interactions between streptomycin sulphate and aqueous food acids (L-ascorbic acid and citric acid): Physico-chemical and spectroscopic insights. (December 2020) - Sharma, Taniya; Kumar, Ashwani; Shah, Shahid Shafi; Bamezai, Rajinder K.
Graphical abstract: Highlights: Density, speed of sound and viscosity of ternary systems are investigated. Thermodynamic properties are evaluated for various concentrations and temperatures. UV–visible studies have also been recorded for present systems. The solute behaves as structure maker in the ternary systems. The results are discussed in terms of hydrophilic - ionic interactions. Abstract: Apparent molar volumes, apparent molar isentropic compressibilities and relative viscosities for streptomycin sulphate + aqueous [cosolute (L-ascorbic acid/citric acid)] solutions at different compositions of solute as also cosolute are determined from experimental set of densities, speeds of sound and viscosities collected at different temperatures. Infinite dilution values of apparent molar volumes and apparent molar isentropic compressibilities, using least-squares fittings of appropriate equations, are correlated in terms of solute–solute and solute–solvent interactions. The various parameters in relation to densities and speeds of sound are also evaluated. The viscosity data has been used to determine Falkenhagen coefficient A, viscosity B -coefficients and its transfer parameter. Solvation behaviour of streptomycin sulphate has also been computed. The absorption spectra for both systems have also been recorded with the help of UV–visible spectrophotometer.